Green Business: Technicist Kitsch? - Newton, Tim; Harte, George (Journal of Management Studies, 1997)
In this paper we present a critical analysis of current `green business' literature. We pay particular attention to the strongly evangelical language of the literature, and we consider whether such green evangelism is likely to represent an effective rhetoric strategy. We pursue this theme through exploring arguments for `environmental excellence', organizational `eco‐cultures', and for corporate environmental strategies. We suggest that current prescriptions for `organizational eco‐change' are often buttressed by evangelical rhetoric and are reliant on the assumption that organizations will voluntarily become greener. Given the centrality of voluntarism within this literature, we devote the latter part of the paper to considering its efficacy, and explore the deferred argument that organizational eco‐change will only come about through stronger state regulation.